Statistical methods for communication science - Hayes, Andrew F. (Lawrence Erlbaum Associates, 2005)
Statistical Methods for Communication Science is the only statistical methods volume currently available that focuses exclusively on statistics in communication research. Writing in a straightforward, personal style, author Andrew F. Hayes offers.